A Cleavable Scaffold Strategy for the Synthesis of One-Bead One-Compound Cyclic Peptoid Libraries That Can Be Sequenced By Tandem Mass Spectrometry - Simpson, Levi S. (2012)
Many macrocyclic depsipeptides or related compounds have interesting medicinal properties and often display more favorable pharmacokinetic properties than linear analogues. Therefore, there is considerable interest in the development of large combinatorial libraries of macrocyclic peptidomimetic compounds. However, such molecules cannot be easily sequenced by tandem mass spectrometry, making it difficult to identify hits isolated from library screens using one bead one compound libraries. Here we report a strategy to solve this problem by placing a methionine in both the linker connecting the cyclic molecule to the bead as well as within the cycle itself. Treatment with CNBr both linearizes the molecule at a specific position and releases the molecule from the bead, making its characterization by tandem MALDI mass spectrometry straightforward.